Drilling and Completion Material Management Improvement by Stochastic Modelling (2020)
The understanding of logistic phenomena entails a broad field of variables that relate to a wider set of considerations. There is a trade-off between general logistic models and mixed models. The former tends to underfit the real case scenarios, while the latter have to be carefully designed in order to have a clear managerial process. In this paper, it is considered a situation observed in a remote production field in Colombian East flatlands, Rubiales. In this case, the supply of materials had challenges in delivery opportunity, inventory rotation.